Extended molecular dynamics simulation of the carbon monoxide migration in sperm whale myoglobin - Bossa, C; Anselmi, M; Roccatano, D; Vallone, B; Brunori, M; Di Nola, A.; AMADEI, ANDREA (Biophysical Journal, 2004)
We report the results of an extended molecular dynamics simulation on the migration of photodissociated carbon monoxide in wild-type sperm whale myoglobin. Our results allow following one possible ligand migration dynamics from the distal pocket to the Xe1 cavity via a path involving the other xenon binding cavities and momentarily two additional packing defects along the pathway. Comparison with recent time resolved structural data obtained by Laue crystallography with subnanosecond to millisecond resolution shows a more than satisfactory agreement. In fact, according to time resolved crystallography, CO, after photolysis, can occupy the Xe1 and Xe4 cavities. However, no information on the trajectory of the ligand from the distal pocket to the Xel is available. Our results clearly show one possible path within the protein. In addition, although our data refer to a single trajectory, the local dynamics of the ligand in each cavity is sufficiently equilibrated to obtain local structural and thermodynamic information not accessible to crystallography. In particular, we show that the CO motion and the protein fluctuations are strictly correlated: free energy calculations of the migration between adjacent cavities show that the migration is not a simple diffusion but is kinetically or thermodynamically driven by the collective motions of the protein; conversely, the protein fluctuations are influenced by the ligand in such a way that the opening/closure of the passage between adjacent cavities is strictly correlated to the presence of CO in its proximity. The compatibility between time resolved crystallographic experiments and molecular dynamics simulations paves the way to a deeper understanding of the role of internal dynamics and packing defects in the control of ligand binding in heme proteins.